Development of a Virtual Instrumentation Platform for an 8/6 SRM (Research, Society and Development, 2022)
The switched reluctance motor (SRM) has been gaining space during the last decades due to the advance of power and control of electronics. Thereby, new researches are emerging in search of methodologies that can increase its efficiency. The objective of this work was the development of a virtual instrumentation starter of an 8/6 SRM, as well as allowing the monitoring of fundamental quantities for studying during the experiments, grouping all the functionalities in a single interface. A robust drive system was used, with the ability to apply the control implemented through the DSP/FPGA from myRIO-1900's. The applied data acquisition system, was composed of position and time sensors conjugate, improving current control and measurement information in real time measurement of quantities. To demonstrate the capacity of the created platform, tests were carried out, activating the 8/6 SRM and collecting the waveforms arranged in the supervisory, which were compared with the signals collected by conventional measuring instruments. The tests showed that the developed platform presented reliable results, with low measurement error, and performed the correct triggering logic.